Privatization and the Role of Sub-National Governments in the Latin American Power Sector: A Plea for Less Subsidiarity? - Sadik-Zada, Elkhan Richard; Löwenstein, Wilhelm; Ferrari, Mattia (International Journal of Energy Economics and Policy, 2018)
In this paper, we explore the cross-national impact of privatization in the network industries on the access to network services. We focus on the assessment of the electricity sector in 20 Latin American countries and analyze the time series between 1985 and 2010. To control for the relevance of the subsidiarity (social commons) argument (Byrne and Mun, 2001; 2003) we assess the interaction between commodification and the role of the sub-national governments in the power sector. Privatization has a statistically significant positive effect on the level of electricity access. In the absence of federalism, privatization in the electricity sector has a greater impact on electrification than in the case with federalist government system. Federalism has a positive impact on the electricity access if electricity is generated and supplied mainly by the state-owned enterprises. Another interesting finding is the relationship between the degree of subsidiarity and electrification: A higher the degree of subsidiarity has a negative effect on the electrification. This could be a result of the increasing transaction costs and rent-seeking behavior in the decentralized settings. The study complements the existing literature by analyzing the privatization reform from the subsidiarity perspective. Keywords: Privatization, Federalism, Subsidiarity, Power Sector, Latin America, Commodification JEL Classifications: D40, E02, H13, H40, H70, L33, L43, L94